IL-10 Dysregulation in Acute Mountain Sickness Revealed by Transcriptome Analysis - Liu, Bao; Chen, Jian; Zhang, Long; Gao, Yixing; Cui, Jianhua; Zhang, Erlong; Xu, Gang; Liang, Yan; Liang, Yu; Wang, Jian; Gao, Yuqi (Frontiers in Immunology, 2017)
Abstract Acute mountain sickness (AMS), which may progress to life-threatening high altitude cerebral edema, is a major threat to millions of people who live in or travel to high altitude. Although studies have revealed the risk factors and pathophysiology theories of AMS, the molecular mechanisms of it do not comprehensively illustrate. Here, we used a system-level methodology, RNA sequencing, to explore the molecular mechanisms of AMS at genome-wide level in 10 individuals. After exposure to high altitude, a total of 1,164 and 1,322 differentially expressed transcripts were identified in AMS and non-AMS groups, respectively. Among them, only 328 common transcripts presented between the two groups. Immune and inflammatory responses were overrepresented in participants with AMS, but not in non-AMS individuals. Anti-inflammatory cytokine IL10 and inflammation cytokines IF17F and CCL8 exhibited significantly different genetic connectivity in AMS compared to that of non-AMS individuals based on network analysis. IL10 was down-regulated and both IF17F and CCL8 were un-regulated in AMS individuals. Moreover, the serum concentration of IL10 significantly decreased in AMS patients after exposure to high altitude (p = 0.001) in another population (n=22). There was a large negative correlation between the changes of IL10 concentration, r(22) = -0.52, p = 0.013, and Lake Louise Score. Taken together, our analysis provides unprecedented characterization of AMS transcriptome and identifies that genes involved in immune and inflammatory responses were disturbed in AMS individuals by high altitude exposure. The reduction of IL10 after exposure to high altitude was associated with AMS.